Kadastro hukukunda hak düşürücü süre - Aksu, Ferda (My University, 2003)
Cumhuriyet döneminde ekonomik, sosyal ve kültürel alanlardaki atılım ve gelişmelere paralel olarak ülke topraklarını hukuki durumlarına uygun bir biçimde haritaya bağlamak amacıyla kadastro faaliyetleri başlamıştır. Bu amaçla çıkarılan 2613 sayılı Kanun ile il ve ilçe belediye hudutları içindeki taşınmazların ve sırasıyla 5602, 509 ve 766 sayılı Kanunlar ile de il ve ilçe belediye hudutları dışında kalan taşınmazların kadastrolanmasına başlanmıştır. Aynı anda il ve ilçe belediye hudut çizgisinin iki tarafında farklı düzenlemeler içeren farklı kanunların uygulanması, kişiler arasında eşitsizliklere ve bunun sonucu olarak huzursuzluklara neden olduğundan, 1987 yılında yürürlüğe giren ve halen de yürürlükte bulunan 3402 sayılı Kadastro Kanunu ile söz konusu kanunlar birleştirilmiş ve kadastro faaliyetlerinin düzenlenmesinde kanunlar arasında birlik sağlanmıştır. Kadastro faaliyetlerini düzenleyen kanunlar arasında hak düşürücü süre yönünden mevcut farklılık 3402 sayılı Kanunla ortadan kaldırılarak, kadastro tutanaklarının kesinleşmesinden itibaren on yıl geçtikten sonra kadastrodan önceki hukuki sebeplere dayanılarak dava açılamayacağı 12/ 3. medde ile hükme bağlanmıştır. 3402 sayılı Kanunun 12/ 3. maddesi ile getirilen on yıllık hak düşürücü süre yanında, bu kanundan önce yürürlükte olan kanunların içerdiği farklı düzenlemelerin yol açtığı ve kişiler arasında eşitsizliğe neden olan sonuçları ortadan kaldırmak amacıyla ek geçici madde 4/ 3 ve 46. madde ile de hak düşürücü süreler öngörülmüştür. Kadastro hukukunda hak düşürücü süre ile ilgili bu üç madde bu tezde açıklanmaya çalışılacaktır. Name and Surname: Ferda Aksu Field: Law Programme: Private Law Supervisor: Professor O. Gökhan Antalya Degree Awarded and Date: Master - April 2003 LACHES IN LAND SURVEY LAW In the Republic period, parallel to the developments and leaps in economical, social and cultural fields, the activities of land surveying of the country lands in the purpose of to fix the country lands to the map which is proper to her juristic situation been started. With the 2613 numbered Statute which is legislated for this aim, it was started to land surveying of the real estates within the borders of the province, district municipalities and in order with the 5602, 509 and 766 numbered Statutes the real estates which exist outside of the province and district municipalities has been land surveyed. The application of different statutes which includes different arrangements at the both sides of the province and district municipality borderline at the same time caused unequalities between the persons and as a result uneasiness appeared; with the 3402 numbered Statute which has come into force in 1987 and still has been in force, the mentioned statutes have been consolidated and the union has accomplished between statutes about arrangement of the land survey activities. The difference about the laches between the statutes arranging the land survey activities removed with the 3402 numbered Statute and it is arrived to a decision that there can not be taken legal action based on the juristic reasons before the land survey after 10 years passed from the land survey minutes becoming definite. In addition to the 10 years of laches brought by the 12/ 3 Article of the 3402 numbered Statute, for the aim of to remove the results caused unequalities between the persons as a reason of the statutes including different arrangements which were in force before this statute, there has been anticipated laches with various articles like Article 4/ 3 and Article 46 of The Land Survey Statue. These three articles about laches in the land survey law are going to be explained in this thesis.
Keywords: Özel Hukuk